2005
DOI: 10.1002/hed.20279
|View full text |Cite
|
Sign up to set email alerts
|

Defining risk levels in locally advanced head and neck cancers: A comparative analysis of concurrent postoperative radiation plus chemotherapy trials of the EORTC (#22931) and RTOG (# 9501)

Abstract: Subject to the usual caveats of retrospective subgroup analysis, our data suggest that in locally advanced head and neck cancer, microscopically involved resection margins and extracapsular spread of tumor from neck nodes are the most significant prognostic factors for poor outcome. The addition of concomitant cisplatin to postoperative radiotherapy improves outcome in patients with one or both of these risk factors who are medically fit to receive chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
1,119
6
30

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,500 publications
(1,191 citation statements)
references
References 13 publications
36
1,119
6
30
Order By: Relevance
“…Consequently, patients can be treated with an appropriate adequate post-operative therapy on the basis of pathological evaluation. Bernier reported that the addition of concomitant cisplatin to postoperative radiotherapy improves outcomes in patients with ECS who are medically fit to receive chemotherapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, patients can be treated with an appropriate adequate post-operative therapy on the basis of pathological evaluation. Bernier reported that the addition of concomitant cisplatin to postoperative radiotherapy improves outcomes in patients with ECS who are medically fit to receive chemotherapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively recent, prospective, randomized controlled trial conducted by the European Organization for Research and Treatment of Cancer (EORTC) suggested that intensification of therapy, not only with PORT but also with concomitant chemotherapy, is warranted with a margin <5 mm in head and neck SCC, including SCC of the oral cavity. 1,3 Another trial conducted in parallel by the US Radiation Therapy Oncology Group (RTOG) supported the role of CERT for high-risk margins, which, however, was defined as tumor at the resected margin. 2 Note that, in addition to margin status, the EORTC trial defined high risk as extracapsular extension (ECE) of lymph node disease, clinical involvement of lymph nodes There was a strong association between the number of adverse features and local control.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of positive margins on further therapy reported by Binahmed et al [10] suggests that the patients with positive margins did not significantly benefit from radiotherapy alone and recurrences among them were greater than the patients with initial clear margins, kovacs et al has reported better survival rates with chemo radiotherapy in such instances [16]. Combined analysis of RTOG and EROTC trials suggests improved outcome of patients with involved margin and perinodal spread on delivery of adjuvant concurrent chemo radiation [17].…”
Section: Discussionmentioning
confidence: 99%